2022
DOI: 10.1186/s12905-022-01935-3
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and factors associated with induced abortion among female students ‘of Private Colleges in Ambo town, Oromia regional state, Ethiopia: a cross-sectional study

Abstract: Background Around 73 million induced abortions take place worldwide each year. Six out of 10 (61%) of all unintended pregnancies, and 3 out of 10 (29%) of all pregnancies, end in induced abortion. In Africa, nearly half of all abortions occur under the least safe circumstances. In Ethiopia 35% of women obtaining induced abortions service. Therefore, thisstudy aims to assess knowledge, attitude, and associated factors towards induced abortion serviceamong female students of private Colleges in A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…A theoretically informed set of demographic, social, and behavioral factors-including age (Bantie et al 2020;Cresswell et al 2016); educational attainment (Kavanaugh et al 2013;Mosley et al 2017); household wealth (Thomas, Norris, and Gallo 2017); place of residence (Holcombe, Berhe, and Cherie 2015;Scoglio and Nayak 2023;Smith et al 2022); religiosity (Biggs et al 2023;Gutema and Dina 2022;Silva et al 2009); and pregnancy/fertility experiences (Moore et al 2015;Woodruff et al 2018)-were identified a priori from the extant literature and assessed independently of other covariates in mixture modeling. Measured predictors of latent class membership included parity (nulliparous vs. multiparous); future fertility intentions (desires no [more] child [ren] or undecided vs. desires a[nother] child [ren]); current contraceptive use (any modern contraceptive use vs. no contraceptive use or traditional methods only); number of family planning (FP) message sources (i.e., radio, television, newspaper/print media, community events) recalled in the past three months (range: 0-4); religiosity, measured continuously using a three-item, 5-point (definitely not true to definitely true) scale assessing the depth and magnitude of participation in religious activities (Cronbach's alpha: 0.88) (Gallagher 2018); and perceived immorality of abortion (endorsement of the statement, "Abortion is immoral"), measured ordinally on a 5-point scale (strongly disagree to strongly agree).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A theoretically informed set of demographic, social, and behavioral factors-including age (Bantie et al 2020;Cresswell et al 2016); educational attainment (Kavanaugh et al 2013;Mosley et al 2017); household wealth (Thomas, Norris, and Gallo 2017); place of residence (Holcombe, Berhe, and Cherie 2015;Scoglio and Nayak 2023;Smith et al 2022); religiosity (Biggs et al 2023;Gutema and Dina 2022;Silva et al 2009); and pregnancy/fertility experiences (Moore et al 2015;Woodruff et al 2018)-were identified a priori from the extant literature and assessed independently of other covariates in mixture modeling. Measured predictors of latent class membership included parity (nulliparous vs. multiparous); future fertility intentions (desires no [more] child [ren] or undecided vs. desires a[nother] child [ren]); current contraceptive use (any modern contraceptive use vs. no contraceptive use or traditional methods only); number of family planning (FP) message sources (i.e., radio, television, newspaper/print media, community events) recalled in the past three months (range: 0-4); religiosity, measured continuously using a three-item, 5-point (definitely not true to definitely true) scale assessing the depth and magnitude of participation in religious activities (Cronbach's alpha: 0.88) (Gallagher 2018); and perceived immorality of abortion (endorsement of the statement, "Abortion is immoral"), measured ordinally on a 5-point scale (strongly disagree to strongly agree).…”
Section: Discussionmentioning
confidence: 99%
“…2022); religiosity (Biggs et al. 2023; Gutema and Dina 2022; Silva et al. 2009); and pregnancy/fertility experiences (Moore et al.…”
Section: Methodsmentioning
confidence: 99%
“…Further, a woman's marital status, her decision-making regarding family size, and the gender composition of her existing children contribute to her vulnerability to unsafe abortions [21,24,25]. Furthermore, attitudes of abortion were found to be influenced by additional factors, including ethnicity, religion, age, the number of children a family has, individual exposure, and personal experiences related to the issue [26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Induced abortion is characterized by the deliberate termination of pregnancy and represents a prevalent reproductive phenomenon, with an annual occurrence exceeding 73 million instances [1]. During the period from 2015 to 2019, it is estimated that approximately 48% (equivalent to 121 million) of all pregnancies globally were unintended.…”
Section: Introductionmentioning
confidence: 99%